Modelación de una prima de seguros mediante la aplicación de métodos actuariales, teoría de fallas y Black-Scholes en la salud en Colombia; Modelling of an insurance premium through the application of actuarial methods, failure theory and Black-Scholes in the health in Colombia - Juan Fernando Salazar García; Diana Sirley Guzmán Aguilar; Daniel Arturo Hoyos Nieto (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– The pricing's premium in an insurance for the health sector is influenced by the claims ratio of its subscribers, which generates high levels of fluctuation and uncertainty. The objective of this research is the application of the actuarial individual risk models, collective risk and credibility model, together with the application of the failure rate technological model and the Black-Scholes financial options model as tools for estimating pricing's premium for the insurance and health industry in Colombia. Based on the claims and the total costs of the historical claims, the models are applied to ensure optimal premiums for coverage of the aggregate losses of the claims. In the end, comparing these models and approaching a definition of an optimal method. The importance of the research settles in the high commitment, responsibility and financial impact of managing and mitigating the impact of actuarial risk, proposing new methodologies through an optimal estimation level in premiums to certify proper functioning of the sector entities in matters of costs, sustainability and service compliance in the sector.
Keywords: D91; G12; G22; G52; I12; 330; insurance premium; actuarial studies; individual risk model; collective risk model; failure rate; credibility theory; valuation of financial assets; aggregate claim amount